2014
DOI: 10.15376/biores.9.4.7311-7325
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Rubber Seed Shell Flour-Filled Polypropylene Composites: The Effect of Poly(ethylene co-Acrylic Acid)

Abstract: The effect of adding poly(ethylene co-acrylic acid) (PE-co-AA) in rubber seed shell flour (RSSF)-filled polypropylene (PP) composites on processing, mechanical, water absorption, and morphological properties was studied. The addition of PE-co-AA increased the processing torque in PP/RSSF composites. Furthermore, mechanical properties such as tensile strength, flexural strength impact strength, Young's modulus, and flexural modulus show significant improvement compared to uncompatibilized composites, while elon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Agro-waste composites offer excellent engineering potential because they are light-weight, environmentally friendly, economical, renewable, and abundant and have high strength and rigidity, and they provide a plausible environmental solution to municipal waste disposal (Pirayesh et al 2012;Zahedi et al 2015). Some combinations of agricultural wastes such as palm kernel shell, coconut shell, walnut shell flour, cocoa pod husk, oil palm agro wastes, peanut shell, rubber seed shell flour, almond shell flour, and thermoplastic materials have been successfully developed (Malkapuram et al 2009;Pirayesh et al 2012;Pirayesh et al 2013;Chun et al 2013;Salmah and Ismail 2013;Obasi et al 2014;Zaaba et al 2014;Mohd Suhaimi and Ismail 2014;Zahedi et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Agro-waste composites offer excellent engineering potential because they are light-weight, environmentally friendly, economical, renewable, and abundant and have high strength and rigidity, and they provide a plausible environmental solution to municipal waste disposal (Pirayesh et al 2012;Zahedi et al 2015). Some combinations of agricultural wastes such as palm kernel shell, coconut shell, walnut shell flour, cocoa pod husk, oil palm agro wastes, peanut shell, rubber seed shell flour, almond shell flour, and thermoplastic materials have been successfully developed (Malkapuram et al 2009;Pirayesh et al 2012;Pirayesh et al 2013;Chun et al 2013;Salmah and Ismail 2013;Obasi et al 2014;Zaaba et al 2014;Mohd Suhaimi and Ismail 2014;Zahedi et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported the use of untreated and carbonized rubber seed powder as reinforcement in polymeric composites. [4] It was reported that carbonized rubber seed shell had the potential as reinforcing filler for natural rubber compounds [5]. In the study of PP-and HDPE-based composites added with RSSP, it was shown that with higher RSSF content, the higher thermal stability, initial degradation temperature, degradation temperature, and total weight loss became.…”
Section: Introductionmentioning
confidence: 99%